Determining the environmentally friendly locations of gas stations within urban areas in Al-Safa district, Jeddah - Al-Dogel, Reem Khalid; Al-Sulami, Morshid (Journal of Humanities & Social Sciences, 2022)
This study aims to determine the environmentally appropriate locations for gas stations in the Al- Safa neighborhood, and to reach that, we must know the locations of the current gas stations and detect the locations of residential clusters, and then classify the criteria to be followed when the gas station is established to finally reach the best locations for the gas stations. This was done by comprehensive inventory and field visits to monitor the location of gas stations, and to sign these stations on the neighborhood map, and to analyse their locations using ARC GIS and satellite images, so we could be able to reach environmentally and healthily suitable areas for fuel stations within the neighborhood. The results showed that the number of petrol stations in Safa neighborhood is twenty- eight. The study showed that gas stations are overlapping and very close to each other. It also showed from this study that there are three petrol stations less than 100 meters from schools, three medical centers, and three wedding palace stations, in addition to the proximity of most petrol stations to residential use, which may be a cause for concern for the health and lives of the population. Therefore, the researcher worked to determine the most environmentally appropriate locations for gas stations. The analysis of environmental convenience shows that stations located in suitable areas are 1,the Peace Station in Al- Safa district 2,the plane station in Al- Safa district 3,Al- Drees Station in Al- Safa District 4,Sasco station in Al- Safa district. Also, most of the suitable lands tend to be on the outskirts of the neighbourhood, while the overcrowding of the stations lies inside, and the lands which are suitable for the operation of fuel stations within the neighbourhood has amounted thirty eight plots. This study recommends that geographic information systems (GIS) should be used when planning a residential neighborhood, especially when choosing the appropriate location for fuel stations ,and focus on alternative uses of petrol and diesel, which could mitigate the damage by reducing the number of gas stations as well as trying to find other transport routes within the city, such as the operation of a pedestrian traffic network and entice the populations to move by public transportation within the city of Jeddah.